Effect of Sulphur on Plant Growth & Defense System Against Salinity Stress - Ibrahim, Saima; Naz, Faiza (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
The given investigation was undertaken to evaluate the performance of black gram (vigna mungo L.) under different salinity levels (i.e. 50mM, 100mM and 150mM NaCl) and to find out the remedial effect of two doses of S (i.e. 2mM and 4mM) against salinity stress on growth of studied crop by providing tolerance against salinity stress. The experiment was carried out in Botany department, Jinnah University for women, Nazimabad, Karachi, in controlled laboratory condition by using plate culture technique followed as completely randomized design with three replication of each treatment. The observation of given research showed that the percentages of shoot and root length and Fresh and dry seedling weights were higher in control treatment. The low (50mM NaCl) level of salinity treatment had no deleterious effects on plant vegetative growth, while at higher concentration of NaCl (100mM), all the growth parameters were drastically reduced. Both application rates of MgSO4 were found satisfactory to eliminate the negative effect of saline environment inside rhizosphere by promoting plant tolerance against stress thus support treated plants growth and development.